The conflict between urban planning and the preservation of sand dunes – The case of the Big Dune in the city of Ashdod, Israel - Haim Tsoar; Aviv Lee Cohen-Zada (City and Environment Interactions, 2020)
The town of Ashdod in Israel has historical roots from the Bronze Age. During the long history, Ashdod was located on a low hill of aeolianite (lithified sand dune) a couple of kilometers east of the sand dunes, while the sand dunes were active because of strong impact of the residents of the town.Modern Ashdod was founded in 1956 as a port city and grew rapidly to become the 6th biggest city of Israel. The city was built on the sand dunes north-west of the ancient town and was divided into seventeen neighborhoods that were built from 1956 until today. Neighborhood 14 was not built until recently because of a bare and active big dune that is located in the northern part of it and the strong pressure made by public and environmental NGOs to preserve it. During the last few years planners have suggested several plans to preserve the dune and to build around it in such a way that the dune will continue to be accessible to the public.This paper explains how the Big Dune was formed and why it is the only active dune in the area. Eight aerial photographs taken in 38 years were used to calculate the rate of advance of the Big Dune and the potential hazard of this dune to neighborhood 14 and the neighborhood north of the dune. We suggest some solutions to solve this problem and how to reduce the rate of advance. Leaving a shifting sand dune in the city is a risk that should be avoided.